Measuring maximal horizontal deceleration ability using radar technology: reliability and sensitivity of kinematic and kinetic variables - Harper, D. J.; Morin, J.-B.; Carling, C.; Kiely, J. (Sports Biomechanics, 2023)
Radar technology has the potential for providing new insights into maximal horizontal deceleration ability. This study aimed to investigate the intra- and inter-day reliability and sensitivity of kinematic and kinetic variables obtained from a novel, maximal horizontal deceleration test, using radar technology. Thirty-eight university sport athletes completed testing for intra-day analysis. Twelve of these participants also completed the deceleration test on a second day for inter-day analysis. The maximal horizontal deceleration test required participants to decelerate maximally following 20 m maximal horizontal sprint acceleration. Reliability was assessed using the intraclass correlation coefficient (ICC) and coefficient of variation (CV%). Sensitivity was evaluated by comparing typical error (TE) to the smallest worthwhile change (SWC). A number of kinematic and kinetic variables had good (ICC > 0.75, CV < 10%) overall intra-day reliability, and were sensitive to detect small-to-moderate changes in deceleration performance after a single familiarisation session. Only kinetic variables had good overall inter-day reliability and were sensitive to detect moderate changes in deceleration performance. The utilisation of this test protocol to assess maximal horizontal deceleration can provide new insights into individual maximal horizontal deceleration capabilities. Future work using this or similar approaches may provide insights into the neuromuscular performance qualities needed to decelerate maximally.